2022
DOI: 10.3390/en15082777
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Plasma Technology for the Production of Green Hydrogen from Ethanol and Water

Abstract: This study concerns the production of hydrogen from a mixture of ethanol and water. The process was conducted in plasma generated by a spark discharge. The substrates were introduced in the liquid phase into the reactor. The gaseous products formed in the spark reactor were hydrogen, carbon monoxide, carbon dioxide, methane, acetylene, and ethylene. Coke was also produced. The energy efficiency of hydrogen production was 27 mol(H2)/kWh, and it was 36% of the theoretical energy efficiency. The high value of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“… 21 This is due to the presence of several chemical bonds in ethanol that are weaker than the chemical bonds in water. 14 , 22 25 Therefore, several products can be formed from ethanol. In the dehydration reaction ( eq 8 ), ethylene is formed, which, in subsequent reactions, produces acetylene ( eq 9 ) and coke ( eq 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 21 This is due to the presence of several chemical bonds in ethanol that are weaker than the chemical bonds in water. 14 , 22 25 Therefore, several products can be formed from ethanol. In the dehydration reaction ( eq 8 ), ethylene is formed, which, in subsequent reactions, produces acetylene ( eq 9 ) and coke ( eq 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Computer simulations also showed that the dissociation rate constant of ethanol in collisions with electrons is many times greater than the dissociation rate constant of water . This is due to the presence of several chemical bonds in ethanol that are weaker than the chemical bonds in water. , Therefore, several products can be formed from ethanol. In the dehydration reaction (eq ), ethylene is formed, which, in subsequent reactions, produces acetylene (eq ) and coke (eq ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrogen production has been extensively investigated by researchers from various fields owing to its potential applications in fuel cell vehicles, public facilities, and industry, etc to replace fossil fuel energy and to reduce the emission of greenhouse gases and pollution in the environment [1][2][3][4]. As a hydrogen-containing industrial product, hydrogen sulfide (H 2 S) is one of the main by-products in the process of petroleum refining by hydro-desulphurization and in the exploitation of methane in natural gas deposits (up to 45% by weight in some deposits).…”
Section: Introductionmentioning
confidence: 99%